The effect of resistance band training on the accuracy of underhand passing reception in female volleyball athletes - Widayat, Rachmad Agung; Harmono, Bayu Akbar; Nuryadi, Achmad; Darisman, Eka Kurnia (Sriwijaya Journal of Sport, 2026)
Research Problems: The underhand passing ability of the women’s volleyball athletes is less accurate, which affects the setter in organising the attack pattern. To improve the accuracy of this technique, an appropriate training method is essential. Research Objectives: This study aims to examine the effectiveness of resistance band training in enhancing the accuracy of forearm passing among female volleyball athletes at the Garuda Delta Sidoarjo club. Method: The research employed an experimental method using a one-group pretest-posttest design involving 20 female athletes. Accuracy was measured using the wall volley passing drill before and after the training intervention. Results: The analysis showed a significant improvement in forearm passing accuracy, with a significance value of 0.001 (p < 0.05). The average score increased from 71.95 (categorised as fair) to 87.05 (categorised as good) following the training. Conclusion: These findings indicate that resistance band training is an effective method for improving the accuracy of basic forearm passing techniques. The results can serve as a reference for coaches in designing more effective volleyball training programs.